A Facile, Fabric Compatible, and Flexible Borophene Nanocomposites for Self‐Powered Smart Assistive and Wound Healing Applications. Issue 22 (3rd June 2022) - Chen, Shuo‐Wen; Huang, Shih‐Min; Wu, Han‐Song; Pan, Wei‐Pang; Wei, Shih‐Min; Peng, Chih‐Wei; Ni, I‐Chih; Murti, Bayu Tri; Tsai, Meng‐Lin; Wu, Chih‐I; Yang, Po‐Kang
Abstract: Smart fabrics that can harvest ambient energy and provide diverse sensing functionality via triboelectric effects have evoked great interest for next‐generation healthcare electronics. Herein, a novel borophene/ecoflex nanocomposite is developed as a promising triboelectric material with tailorability, durability, mechanical stability, and flexibility. The addition of borophene nanosheets enables the borophene/ecoflex nanocomposite to exhibit tunable surface triboelectricity investigated by Kelvin probe force microscopy. The borophene/ecoflex nanocomposite is further fabricated into a fabric‐based triboelectric nanogenerator (B‐TENG) for mechanical energy harvesting, medical assistive system, and wound healing applications. The durability of B‐TENG provides consistent output performance even after severe deformation treatments, such as folding, stretching, twisting, and washing procedures. Moreover, the B‐TENG is integrated into a smart keyboard configuration combined with a robotic system to perform an upper‐limb medical assistive interface. Furthermore, the B‐TENG is also applied as an active gait phase sensing system for instantaneous lower‐limb gait phase visualization. Most importantly, the B‐TENG can be regarded as a self‐powered in vitro electrical stimulation device to conduct continuous wound monitoring and therapy. The as‐designed B‐TENG not only demonstrates great potential for multifunctional self‐powered healthcare sensors, but also for the promising advancements toward wearable medical assistive and therapeutic systems. Abstract : The development of novel borophene/ecoflex nanocomposite as a new triboelectric layer with excellent stability, flexibility, durability, and triboelectricity is demonstrated. The addition of borophene nanosheets strongly enhances the triboelectric charge transfer process. The borophene/ecoflex is further integrated into a B‐TENG for biomechanical energy harvesting, biomedical assistive platform, and wound healing applications.